Effectiveness of Student Learning Outcomes Through Numbered Head Together Method Theme of Changes in The Appearance of The Earth and Sky - Fitriani, Ika Nur; Ridhani, Jovita (Indonesian Journal of Learning and Instructional Innovation, 2025)
This research was motivated by the lack of understanding of students in the natural science material in grade IV Cluster II Ahmad Yani, Surakarta City. Out of 150 students, only 32% of students exceeded the minimum completeness criteria; on the other hand, 68% of students still had results that were still less than the minimum completeness criteria. The causative factor is the way teachers teach, which is not varied and tends to be boring. Teachers teach more in conventional ways, so students become fixated and less active during learning. The purpose of the research is to increase student learning outcomes on the numbered head together practice model directly with globe and flashlight media and to find out the process of day and night and to find out whether this model can run well. This research is classified as classroom action research that uses 2 cycles. Cycle 1 will be held on May 6, 2024, and cycle 2 will be held the following month, on June 3, 2024. Based on the results of the research on the numbered head together learning model, the results of the students' study can increase students' understanding of the lesson of changes in the appearance of the earth and sky. This is evidenced by the development of the percentage of student learning completeness starting from the first cycle, where only 32% increased to 79%. So, in cycle 2 completeness has been classically achieved. It can be concluded that the numbered head together learning model and using media can increase students' understanding and improve student learning outcomes on the lesson of changes in the appearance of the earth and sky.